Good Corporate Governance As A Moderating Variable Of The Influence Of Green Accounting Variables On Environmental Performance - Kusiyah; Rieneke Ryke Kalalo; Arifia Nurriqli; Loso Judijanto; Mega Arisia Dewi (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This research is a quantitative study with an explanatory approach, which uses the three studies mentioned above as a fundamental basis for creating hypotheses, building hypotheses accompanied by arguments, and testing the hypotheses. Research data is needed to confirm the hypothesis. The research data used in this article is primary data that researchers obtained from ten environmental managers at BUMN companies under Rajwali Nusantra Indonesia. The data obtained by the researcher contains ten questions, including four questions about Green Accounting, four about Environmental Performance, and two about Good Corporate Governance. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The results in this article show that all hypotheses in this study can be accepted and proven. In the first hypothesis in this study, the Green Accounting variable can have a positive relationship direction and a significant influence on Environmental Performance. This is because the  ​​P-value is positive and is below the significance level of 0.05, namely 0.003. These results mean that the better the Green Accounting is, the more funds a company can save on environmental expenditures, such as environmental accidents, and so on. This can improve Environmental Performance. In the following hypothesis, the Good Corporate Governance variable can also strengthen the influence of the Green Accounting variable on Environmental Performance. The same thing indicates this: the  ​​P-value in the second column is positive and below the significance level of 0.05, namely 0.000.